2007
DOI: 10.3149/thy.0102.191
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Conflict Scale for Adolescents

Abstract: This study investigated the Gender Role Conflict Scale-Adolescent Version (GRCS-A) and its relationship with the Gender Role Conflict Scale (GRCS), the measure from which it was adapted. Significant correlations between the adult and adolescent versions provided support for the concurrent validity of the GRCS-A. Further analyses revealed that two other measures of male masculinity, the Adolescent Masculinity Ideology in Relationships Scale (AMIRS) and Male Role Attitudes Scale (MRAS), are also significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This provided another way to explore the etiology and impact of challenges for males, partially from a dynamic perspective. Studies have suggested that increased scores on the Gender Role Conflict Scale for Adolescents are related to intrapsychic and interpersonal conflict (Blazina, Cordova, Pisecco, & Settle, 2007;O'Neil, 2008).…”
Section: Males' Early Life Experiencesmentioning
confidence: 99%
“…This provided another way to explore the etiology and impact of challenges for males, partially from a dynamic perspective. Studies have suggested that increased scores on the Gender Role Conflict Scale for Adolescents are related to intrapsychic and interpersonal conflict (Blazina, Cordova, Pisecco, & Settle, 2007;O'Neil, 2008).…”
Section: Males' Early Life Experiencesmentioning
confidence: 99%
“…Since GRC was first conceptualised in the early 1980s [ 52 ], researchers have considered the extent of the impact gender role socialisation has on men's behaviour and wellbeing [ [52] , [53] , [54] ]. The detrimental impact of GRC on social and psychological health is also well-documented [ [55] , [56] , [57] ]. Research on the link between GRC and anxiety is somewhat limited.…”
Section: Introductionmentioning
confidence: 99%